Metamaterial Sensors - Jing Jing Yang; Ming Huang; Hao Tang; Jia Zeng; Ling Dong (International Journal of Antennas and Propagation)
Metamaterials have attracted a great deal of attention due to their intriguing properties, as well as the large potential applications for designing functional devices. In this paper, we review the current status of metamaterial sensors, with an emphasis on the evanescent wave amplification and the accompanying local field enhancement characteristics. Examples of the sensors are given to illustrate the principle and the performance of the metamaterial sensor. The paper concludes with an optimistic outlook regarding the future of metamaterial sensor.